ANALISIS SIKAP LINGKUNGAN DI MASYARAKAT KAWASAN PABRIK TAHU KABUPATEN MALANG - Purwaning Budi Lestari; Tri Asih Wahyu Hartati; Ardian Anjar Pangestuti (JPM PAMBUDI, 2021)
The purpose of this community service activity is to describe environmental attitudes in the community in the tofu factory area, Karangploso District, Malang Regency. The method of carrying out activities is through the survey method. Data analysis used descriptive statistics by looking at the percentage and average. The population used is residents around the tofu factory, Karangploso District, Malang Regency, with a sampling technique through accidental sampling. The instrument used is an attitude scale questionnaire, interviews. Based on the results of the description, the average environmental attitude indicator shows the following criteria: the 'High' criterion is indicated by the attitude indicator number 1,3,7,15, then the 'Medium' criterion is indicated by the attitude indicator number 5,9,14, the 'Low' criterion is found. on the attitude indicator number 2,8,10, 12,13, then the 'Very Low' criterion is indicated by the attitude indicator number 4 with an average of 1,7. The conclusion of the environmental attitude of the community wants the need for an increase in waste management in the tofu factory area in Malang Regency.